ANALISIS PUTUSAN NOMOR 26/PDT.SUS-PAILIT/2021/PN SMG TENTANG PERMOHONAN PAILIT PT. NUSANTARA SINERGI LOGISTIK YANG DIAJUKAN OLEH KREDITUR: Analysis Of Decision Number 26/PDT.SUS-PAILIT/2021/PN SMG Regarding The Bankruptcy Petition Against PT. Nusantara Sinergi Logistik Filed By A Creditor - Utomo, Prihady (Jurnal Globalisasi Hukum., 2025)
Bankruptcy reflects a debtor’s inability to fulfill debt payment obligations to more than one creditor, “as stipulated in Article 2 paragraph (1) of the Bankruptcy Law”. The bankruptcy petition procedure is formal in nature, and the judge is obligated to grant the petition if there is simple evidence that the requirements have been fulfilled. However, in practice, there are cases where bankruptcy petitions are rejected, such as in the dispute between the creditors and PT. Nusantara Sinergi Logistik. The issue arises whether the relatively small amount of debt can serve as a valid reason to reject a bankruptcy petition and whether such a decision reflects the principle of justice. This research is normative in nature with a descriptive approach, utilizing secondary data and analyzed qualitatively. The research results indicate that if a debtor has more than one creditor and is unable to repay debts that have matured and are collectible, then bankruptcy can be granted “based on Article 2 paragraph (1) and Article 8 paragraph (4) of the Bankruptcy Law”. The use of a "small amount" of debt as the basis for rejection has the potential to violate the principle of justice for creditors and to weaken legal protection over legitimate claims.